2018
DOI: 10.1177/1082013218788753
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatments on the structure and emulsifying properties of protein isolates from cumin seeds (Cuminum cyminum)

Abstract: The effect of heat treatments (65, 75, 85, and 95 ℃, 30 min) on the structure and the emulsifying properties of cumin protein isolates were investigated. The fluorescence spectra analysis showed that the conformations were remarkably influenced by heat treatments. An increase in the ratio of α-helix in the secondary structure of heated cumin protein isolates was observed from the result of circular dichroism. Thermal treatments at different temperatures led to an increase in the surface hydrophobicity ( H) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 47 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…Therefore, research on the effects of different treatments on the structural and functional properties of food proteins is essential to better understand their roles in food systems. Various treatments such as heat [ 11 ], ultrasound [ 12 ], high pressure [ 13 ], and pH [ 14 ] significantly affect the structural and functional properties of proteins, among which the heat treatment has been one of the major methods to modify the characteristics of food ingredients and has a great impact on the structural and functional properties of proteins [ 15 ]. What’s more, most food proteins undergo structural transformation during heat processing which could affect the digestion of proteins [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research on the effects of different treatments on the structural and functional properties of food proteins is essential to better understand their roles in food systems. Various treatments such as heat [ 11 ], ultrasound [ 12 ], high pressure [ 13 ], and pH [ 14 ] significantly affect the structural and functional properties of proteins, among which the heat treatment has been one of the major methods to modify the characteristics of food ingredients and has a great impact on the structural and functional properties of proteins [ 15 ]. What’s more, most food proteins undergo structural transformation during heat processing which could affect the digestion of proteins [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…4(B), the particle size of Mb in the T 0 group gradually increased with time. It has been reported that the distribution curves moved to a larger droplet size range and their volume frequency increased with the increase of heating temperature 48 . The natural structure of Mb was broken down under high‐temperature conditions, and this process destroyed the hydrophobic heme molecule aggregates within it, so that the iron porphyrin ring was exposed to the polar environment and Mb was converted to methemoglobin.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, MTG gel is the best in the performance of gel matrix, which indicates that the addition of TG enzyme and Mg 2+ improves the gel performance and forms a more compact and stable gel. With the increase in frequency, the tan δ value of MTG gel changes gently and the slope is close to zero and does not depend on the change in frequency, indicating that the gel has strong gel performance [ 49 ]. Tan δ value of HG gel is about 0.5–0.6, which indicates that the system is a gel characterized by weak elasticity [ 50 ].…”
Section: Results and Analysismentioning
confidence: 99%